Gene Editing in Rabbits: Unique Opportunities for Translational Biomedical Research - Xu, Jie; Zhang, Jifeng; Yang, Dongshan; Song, Jun; Pallas, Brooke; Zhang, Chen; Hu, Jiafen; Peng, Xuwen; Christensen, Neil D.; Han, Renzhi; Chen, Y. Eugene (Frontiers in Genetics, 2021)
The rabbit is a classic animal model for biomedical research, but the production of gene targeted transgenic rabbits had been extremely challenging until the recent advent of gene editing tools. More than fifty gene knockout or knock-in rabbit models have been reported in the past decade. Gene edited (GE) rabbit models, compared to their counterpart mouse models, may offer unique opportunities in translational biomedical research attributed primarily to their relatively large size and long lifespan. More importantly, GE rabbit models have been found to mimic several disease pathologies better than their mouse counterparts particularly in fields focused on genetically inherited diseases, cardiovascular diseases, ocular diseases, and others. In this review we present selected examples of research areas where GE rabbit models are expected to make immediate contributions to the understanding of the pathophysiology of human disease, and support the development of novel therapeutics.